Hydraulic Conductivity of the Permeable Asphalt Pavement – Laboratory vs In Situ Test - Afonso, Márcia Isabel Lopes (2020)
Permeable asphalt pavements (PAP) are a key measure for mitigating the climate change effects in urban areas. Cities are becoming increasingly dense and have large areas of waterproofing due to the excessive construction of buildings and highways that prevent the rainwater drainage into the soil. Recently, the PAP study with a double layer porous asphalt (DLPA) has been an alternative to the use of a porous asphalt single layer (PA), with recognized advantages in increasing water infiltration and, consequently, in decreasing surface runoff. It was developed in field a PAP of small dimensions to assess its capacity to respond to floods. The purpose of this study is to evaluate the hydraulic conductivity (K) of the DLPA applied on the PAP, both in laboratory conditions and in field conditions, and verify the representativeness of the laboratory results in relation to the results obtained in situ. In laboratory terms, the LCS permeameter was used, which evaluates the vertical and horizontal hydraulic conductivity, both in specimens produced in the laboratory and in cores extracted in situ. In the field, the LCS permeameter and the falling head permeameter were used to measure the hydraulic conductivity and the relative hydraulic conductivity (HC), respectively. The laboratory tests were performed according to Standards EN 12697-19 and NLT 327 and the in situ tests according to Standards EN 12697-40 and NLT 327. It was verified that the specimens produced in the laboratory of the two porous layers showed values of K (vertical and horizontal) lower than those obtained in the field cores, both for the individual layers PA and for the DLPA. Thus, it was found that the study in controlled environment differs in terms of results. This divergence justified the need to perform a field study in order to perceive the actual performance of the PAP surface layer. This study was characterized by the values of K (m/s) and HC (s-1), from which it was not possible to obtain a relation. From this study it was concluded that the measuring methods of the hydraulic conductivity in the laboratory were close to the behaviour of the same in situ, however its evaluation under real conditions is always essential.